Pemanfaatan Ekstrak Terung Asam Pada Pakan Buatan Terhadap Pertumbuhan Udang Vaname (Litopenaeus Vannamei) - Linayati Linayati; Restu Puji Astuti; Tri Yusufi Mardiana; Muhammad Bahrus Syakirin; Muhammad Zulkham Yahya; Meilissa Chintya Wijaya (JURNAL LITBANG KOTA PEKALONGAN, 2022)
Abstract  This study aims to determine the effect of tamarind eggplant extract added to feed on the growth of vannamei shrimp and to determine the dose of tamarind eggplant extract which gives the highest growth in vaname shrimp. This research was conducted on 17 December 2020 - 14 January 2021 at the Brackish and Marine Aquaculture Laboratory, Faculty of Fisheries, Pekalongan University, Jalan Pantai Dewi No. 1, Slamaran Pekalongan. The experimental design used was a completely randomized design (CRD) with 4 treatments and 3 replications. Treatment A (0 ml / L sour eggplant extract / kg feed), B (50 ml / L sour eggplant extract / kg feed), C (100 ml / L sour eggplant extract / kg feed), and D (150 ml / L sour eggplant extract / kg of feed). The results showed that the addition of tamarind eggplant extract at different doses to the feed had a very significant effect on the growth of vaname shrimp seeds. Treatment B had the best growth which was 5.05 gr, then treatment C was 4.33 gr, treatment D was 3.99 gr, and the lowest was treatment A was 3.05 gr.   Keywords: Vanname Shrimp, Tamarind Eggplant, Growth